PENGARUH CELEBRITY ENDORSMENT, VARIASI PRODUK, DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN CASE HANDPHONE DI INSTAGRAM ANYACOLECTION (Jurnal Riset Manajemen dan Akuntansi, 2023)
The purpose of this research is to examine the effect of celebrity endorsements, product variety, and product quality on the decision to purchase a mobile phone case at anyacollection_. The population and sample used in this study were coustemers from the anyacolection_ online shop who had bought cell phone case products at anyacolection_. Data collection was carried out by distributing questionnaires with Likert scale measurements. Then, the data testing techniques used in this study were validity and reliability tests, R-Squer tests, and hypothesis testing through bootstrapping using Smart PLS 3.0 software. The results showed that celebrity endorsements and product quality had a positive and significant effect on purchasing decisions, while product variations had a negative effect on purchasing decisions. The better the promotion and the level of product quality, the more it will influence the decision to buy a cellphone case at the anyacollection_ online shop